Identification, Job Satisfaction and Work Motivation among Tutors at the Open University of Israel - Beyth-Marom, Ruth; Harpaz-Gorodeisky, Gal; Bar-Haim, Avaid; Goder, Eti (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2006)
Tutors working for The Open University of Israel (OUI), a distance learning institution, are often the only academic staff who have direct contact with students. Their performance is therefore crucial for the university. The nature of their job, however, might hinder optimal performance: they are temporary and part time employees, and thus have low job security. Their academic freedom is limited and, in most OUI learning centers, they are professionally isolated. These factors can negatively affect tutors' organizational identification, job satisfaction, and motivation. This study is focused on two sets of variables that serve as possible predictors of identification, satisfaction, and motivation: (1) role perceptions (job importance and job richness); and (2) organizational attachment (relations with the university, attentiveness of the university and the university's appreciation of their work). Seventy-one (n = 71) tutors completed a general survey. Regression analysis and path analysis revealed that identification and job satisfaction were well predicted by job importance and organizational attachment, while work motivation was not. Theoretical and practical implications are discussed.